Duration and Intensity of Kindergarten Attendance and Secondary School Track Choice - Tim Landvoigt; Grit Muehler; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This paper investigates the relationship between kindergarten attendance and secondary school track choice in West-Germany. Our analysis is based on a panel of 12 to 14-year olds with information from age two on, drawn from the German SocioEconomic Panel (GSOEP) 1984?2005. We estimate binary probit models to assess the impact of the duration (in years) and the intensity (half-day or full-day) of kindergarten attendance. Our results indicate that kindergarten non-attendance is associated with a significantly lower probability to attend the highest secondary school track (?Gymnasium?). Further, full-day attendance is associated with a decreasing probability of attending the highest secondary school track for every duration of preschool child care. Thus, intensity seems to matter more than duration.
Keywords: J13; J12; I21; 330; kindergarten; preschool education; school placement; Bildungsniveau; Kinderbetreuung; Bildungsverhalten; Schätzung; Deutschland